ANALISIS TINGKAT PELAYANAN PROSES BELAJAR MENGAJAR SECARA ONLINE TERHADAP KEPUASAN MAHASISWA DI FAKULTAS EKONOMI UNIVERSITAS LANCANG KUNING - Wita Dwika Listihana; Arizal N; Zulia Khairani (Universitas Lancang Kuning, 2022)
Efforts to fulfill student desires are the key to success in winning the competition and the best action that needs to be taken by higher education institutions is to use feedback from students to make changes to services. Every student wants maximum satisfaction fromevery service available in educational institutions, with maximum satisfaction obtained by students will be able to improve the quality of educational services. The purpose of this study was to analyze the level of student satisfaction in receiving the online teaching and learning process, to analyze the quality of services provided by education providers to students online. To analyze the effect of the level of service provided by education providers on student satisfaction at the Faculty of Economics, Lancang Kuning University. From the results of the study, it showed that the level of student satisfaction in receiving the teaching and learning process, on average, could be said to be satisfied in accepting online learning. While services for online infrastructure that can be used by students are still not supportive, namely the campus wifi problem. The results of the online teaching and learning process services on student satisfaction which are carried out at the Faculty of Economics have a significant influence on student satisfaction, but there are two variables that are not significant. and has a negative value, namely the responsiveness variable and tangible variable. This is due to the lack of communication between students and the academic community and the lack of equipment available for online learning.